Síntese de 1,1-dimetiletil-1h-pirazóis em líquidos iônicos - Marzari, Mara Regina Bonini (2010)
This work describes the synthesis of a series of pyrazoles from enaminoketones (RC(O)CH=CHNMe2 where R = hexyl, dimethoxymethyl, Ph, 4-Me-C6H4 4-F-C6H4, 4-Cl-C6H4, 4-Br-C6H4, 4-O2N-C6H4, thien-2-yl, fur-2-yl, pyrrol-2-yl, pyridin-2-yl) and N-tert-butilhidrazine hydrochloride. In order to get the best reaction media, reactions were carried out in different ionic liquids such as: [BMIM][BF4], [BMIM][Br], [OMIM][BF4], [BMIM][PF6], [DBMIM][Br], [DBMIM][BF4], [BMIM][OH], [BMIM][SCN], [HMIM][HSO4] and [HMIM][CF3CO2], with different physical and chemical. The behavior of each type of ionic liquid was discussed and the best yield for the cyclocondensation reactions studied was obtained using [BMIM][BF4]. Furthermore, also was a series of pyrazoles from the enones ([CF3C(O)CH=C(R)(OR1], where R1 = Me, Et and R = H, Me, Ph, 4-Me-C6H4, 4-MeOC6H4, 4-F-C6H4, 4-Cl-C6H4, 4-Br-C6H4, fur-2-yl, thien-2-yl and naphthalen-2-yl) and hydrochloride N-tert-butilhydrazine in the presence of pyridine was obtained. The products were obtained as a mixture of isomers. In some cases, it was possible to separate the isomers by washed with hexane. One of the crystalline compounds was analyzed by X-ray diffraction to confirm its structure.